WAKAF PAKAIAN PERSPEKTIF EKONOMI SYARIAH - Akbar, Wahyu (AL-QARDH, 2016)
Clothes as primary necessity is the most needed especially if there is a disaster such as flood, eruption, fire and some other disasters. It is better if the clothes belong to some unlucky people, and it can be through benefaction instrument. So it can create the economy balancing which then be able to make a development of economy equalization, especially the primary needed (daruriyat) it is about clothes needed. It can be as a solution to the overage clothes which had by the rich men and also as a way to consumptive attitude that has been a life style and character of rich men toward clothes trend mode. The main aim of this study was to review the basic problem: (1) What were the economic values which had on the clothes of syariah economy perspectives? (2) How was the clothes benefaction ijtihad of syariah economy perspectives as economy development?This study was a library reseacrh, where specifically it was mentioned as deductive qualitative descriptive design in frame syariah ecoonomy by using histroical approach, conceptual approach, and syariah economy contextual approach, by using deductive qualitative descriptive analysis model, they were data reduction, data display, and verification. Data collected was analyzed by using retropsective method.The results of the study concluded that: (1) the economic values which had on the clothes of syariah economy perspectives were the function value and the benefit of human sustainability guarantee which placed on priority scale of humanâs need. It was primary needed (daruriyat) which can guarantee the equilibrium of doing the life activity whether based on muamalah or worship. (2) the clothes benefaction ijtihad Â of syariah economy perspectives as economy development were through two models they were consumptives benefaction (using directly without any production process) and productive benefaction (processing the clothes which economical) as a relevant idea to the new paradigm of benefaction in Indonesia and also as solution to consumptive attitude of the community toward the dynamic of clothes trend mode.Â Â Â Â Â Â